1997
DOI: 10.1021/bi963025c
|View full text |Cite
|
Sign up to set email alerts
|

Solution Structure of Oxidized Saccharomyces cerevisiae Iso-1-cytochrome c,

Abstract: Proton assignments for the oxidized yeast iso-ferricytochrome c at 303 K Note: The underlined chemical shift values indicate the stereospecific assignments for disastereotopic pairs of methylene protons or isopropyl methyl groups.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

32
153
1

Year Published

1997
1997
2011
2011

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 121 publications
(186 citation statements)
references
References 50 publications
32
153
1
Order By: Relevance
“…Moreover, both structures are, within the indetermination of the family, substantially similar to the corresponding X-ray structures (Baistrocchi et al, 1996;Banci et al, 1997a). The similarity is especially evident for the backbone conformation.…”
Section: Discussionsupporting
confidence: 65%
See 2 more Smart Citations
“…Moreover, both structures are, within the indetermination of the family, substantially similar to the corresponding X-ray structures (Baistrocchi et al, 1996;Banci et al, 1997a). The similarity is especially evident for the backbone conformation.…”
Section: Discussionsupporting
confidence: 65%
“…The results obtained for hh cyt c and for S. cereVisiae cytochrome c (Banci et al, 1997a) are shown in Table 3. They are somewhat different from those already reported (Gao et al, 1990;Turner, 1993) and sensibly different from those calculated from the 13 C data (Turner, 1995).…”
Section: Magnetic Susceptibility Tensormentioning
confidence: 99%
See 1 more Smart Citation
“…The two proteins have a similar tertiary architecture [14][15][16][17], but yeast cyt c displays a significantly lower stability than the protein from horse, it does not bind ATP and, contrary to horse cyt c, lacks pro-apoptotic activity [18,19]. The CL-cyt c binding reaction has been investigated in the absence and in the presence of ATP and sodium chloride, two compounds that significantly influence the (horse cyt c)-CL binding process [5].…”
Section: Introductionmentioning
confidence: 99%
“…The system was studied with both proteins in the reduced state since it was impossible for us to keep one or both proteins in the oxidized state for the long time of the NMR experiments. The characterization of these adducts still has a biological meaning, as the surfaces and their electrostatic potentials are not affected by the redox state (as witnessed by the comparison of the structures in the two states [17,18,19,20]) and therefore are expected to provide relevant information about the adducts. 15 N chemical shifts were monitored through 1 H-15 N HSQC experiments, which are very sensitive and thus relatively quick.…”
Section: Introductionmentioning
confidence: 99%